SIDE WEIR FLOW INVESTIGATION IN A CIRCULAR CHANNEL USING COMPUTATIONAL FLUID DYNAMICS (CFD) FOR SUBCRITICAL FLOW CONDITION - MOHAMMED, JOWHAR R.; SHIBA, SHAMIRAN J. (Journal of Duhok University, 2017)
The 3D flow over side weirs is investigated using Computational Fluid Dynamic (CFD). The study aims to assess the capability of ANSYS CFX code for modeling flow characteristics in a circular channel with side weir for subcritical flow condition. Twelve models were studied for some ranges of variables such as discharge, length and height of side weir. The numerical simulation was based on the solution of continuity and momentum equations for three dimensional, incompressible, steady and turbulent flow. The volume of fluid (VOF) method was used to predict the free surface changes and the RNG k-ε model was employed for simulating the flow field. The experimental data of Uyumaz and Muslu (1985) were used for verification. For all models, the specific energy is obtained and the average energy difference at the upstream and downstream side of the weir was very small and the assumption of constant energy in the circular channel was acceptable. The numerical results predicted the changes in the water surface profile at the main channel central axis and indicated that the water level rises from upstream to downstream end of the weir. The discharge coefficient (Cd) variation with the upstream Froude number (Fr1) for different weir height and length were studied and it was found that the value of (Cd) decreased with the increase of (Fr1) value. For each side weir length, the variation of (Cd) with the ratio of the weir height to channel diameter (P/D) were studied and it was observed that with the increase of (P/D) ratio the value of the (Cd) increased. The relation between the (Cd) and the ratio of the side weir length to channel diameter (L/D) for different weir height were also investigated. It was noticed that the (Cd) value increased gradually as the (L/D) ratio increased. The combined effects of (Fr1), (P/D) and (L/D) on the (Cd) were studied for all models and an empirical expressions for describing this relation was obtained and it was found that (Cd) was a function of all the above parameter.